A new bound for the Jensen gap pertaining twice differentiable functions with applications - Khan, Shahid; Adil Khan, Muhammad; Butt, Saad Ihsan; Chu, Yu-Ming (Advances in difference equations, 2020)
In this paper, we present a new bound for the Jensen gap with the help of a Green function. Using the bound, we deduce a converse of the Hölder inequality as well. Finally, we present some applications of the main result in information theory.